Assessment of haemodynamic stability with intubating dose of intravenous rocuronium bromide versus vecuronium bromide in predominantly stenotic valvular cardiac surgery patients - Bhagade, Priyanka; Wadaskar, Dhawal; Tendolkar, Bharati (International Journal of Research in Medical Sciences, 2017)
Background: In the purely or predominantly mitral stenotic heart surgeries, the principal haemodynamic goals are to maintain a sinus rhythm and avoiding tachycardia. Thus rapid airway control and hemodynamic stability are vital for successful anaesthetic management of patients undergoing the cardiac surgeries. In such patients, muscle relaxants play a pivotal role for achieving good hemodynamic stability. Hence, this study was conducted to evaluate the hemodynamic stability of rocuronium bromide i.v. vecuronium bromide. Methods: The study conducted was randomized prospective double blind study in 60 adult patients (30 in each group) undergoing elective cardiac valvular surgery. Each group received either intubating dose of Rocuronium (0.6 mg/kg body weight) or intubating dose vecuronium (0.1 mg/kg body weight) intravenously after receiving sedation and analgesia. Hemodynamic parameters like heart rate, systolic and diastolic blood pressure, mean arterial pressure and central venous pressure were recorded at baseline 10 minutes after sedation /analgesia at induction, laryngoscopy and at intubation. Any side effects during intubation were noted. Results: Intubating doses of either Rocuronium or vecuronium are not associated with any haemodynamic adverse effects. Also there were no statistically significant (p<0.05) differences between both these groups, in any of the variables at any time. Conclusions: The present study showed that Rocuronium had maintained excellent cardiovascular stability for the dose given to the patient. There was no statistically significant increase in heart rate, systolic, diastolic and mean arterial blood pressure after administration of Rocuronium as compared to vecuronium in the study.